From Boredom to Engagement: The Impact of Kahoot and Quizizz on Students’ Learning Participation in Economics Classes. - Nik Hassan, Nik Suriati; Ab Rani, Nor Zuriati Amani; Zahari, Nor Sabrina; Mohd Hassan, Norsilawati; Zulqernain, Nurul Syaqirah; Zahid, Putra Faizurrahman (International Journal of Accounting, Finance and Business, 2025)
: Game-based learning enhances both enjoyment and effectiveness in the classroom by incorporating elements such as scoring, competition, and teamwork to maintain student engagement and assess knowledge. In this study, Kahoot and Quizizz were used as online tools to reinforce previously learned economics concepts, aiming to reduce boredom and fatigue in online learning environments. The results show that these platforms increased student participation and engagement in class. Furthermore, the study emphasizes the need to equip teaching staff with skills in digital learning tools as game-based learning continues to gain traction in higher education.